Post-licensure safety surveillance of 23-valent pneumococcal polysaccharide vaccine in the Vaccine Adverse Event Reporting System (VAERS), 1990–2013. Issue 25 (27th May 2016) - Miller, Elaine R.; Moro, Pedro L.; Cano, Maria; Lewis, Paige; Bryant-Genevier, Marthe; Shimabukuro, Tom T.
Highlights: No new or unexpected safety concerns were identified after Pneumovax ® 23 vaccine. Fever and injection site reactions were the most commonly reported adverse events. Cellulitis was one of the most commonly reported serious adverse events. Abstract: Background: 23-Valent pneumococcal polysaccharide vaccine, trade name Pneumovax ® 23 (PPSV23), has been used for decades in the Unites States and has an extensive clinical record. However, limited post-licensure safety assessment has been conducted. Objective: To analyze reports submitted to the Vaccine Adverse Event Reporting System (VAERS) following PPSV23 from 1990 to 2013 in order to characterize its safety profile. Methods: We searched the VAERS database for US reports following PPSV23 for persons vaccinated from 1990 to 2013. We assessed safety through: automated analysis of VAERS data, crude adverse event (AE) reporting rates based on PPSV23 doses distributed in the US market, clinical review of death reports and reports involving vaccine administered to pregnant women, and empirical Bayesian data mining to assess for disproportional reporting. Results: During the study period, VAERS received 25, 168 PPSV23 reports; 92% were non-serious, 67% were in females and 86% were in adults aged ≥19 years. When PPSV23 was administered alone, fever (43%), injection site erythema (28%) and injection site pain (25%) were the most commonly reported non-serious AEs in children. Injection site erythema (32%), injection site pain (27%) and injection site swelling (23%) were the most commonly reported non-serious AEs in adults. Of serious reports (2129, 8% of total), fever was most commonly reported in both children (69%) and adults (39%). There were 66 reports of death, four in children and 62 in adults. Clinical review of death reports did not reveal any concerning patterns that would suggest a causal association with PPSV23. No disproportional reporting of unexpected AEs was observed in empirical Bayesian data mining. Conclusions: We did not identify any new or unexpected safety concerns for PPSV23. The VAERS data are consistent with safety data from pre-licensure clinical trials and other post-licensure studies.